Analisis Dampak Pengangguran dan Tingkat Kemiskinan di Provinsi Lampung 2016-2020 - Erica Amalia Saputri; Muhammad Dicki Setiawan; Muhammad Washil Abdul Ghani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The province of Lampung in Indonesia continues to face a great deal of poverty. The purpose of this study is to look at how poverty levels in this area are affected by population (X2) and unemployment (X1). Numerous primary and secondary sources of data are gathered, and relevant statistical techniques are applied to the analysis. The analysis's findings demonstrate that unemployment (X1) significantly affects Lampung's poverty level, with rising unemployment rates being correlated with rising poverty levels. Contrary to predictions, however, population size (X2) does not appear to have a meaningful impact on the amount of poverty. This implies that other variables might have a greater influence on how impoverished this area is. These results have significant ramifications for Lampung's development strategy. The main focus of policy should be on initiatives to lower the unemployment rate by increasing job opportunities for the populace and creating jobs through skill-training programs. Other aspects of poverty, such as access to healthcare and education, should also be taken into consideration.